CRITICAL THEORY AND THE END OF HISTORY THESIS: A COMPARATION - Rifqi Khairul Anam (PT Innovative Academic Journals, 2024)
This paper examines the contrasting perspectives of the Frankfurt School and Francis Fukuyama on the direction and purpose of human history. The Frankfurt School, a group of critical theorists, offered a radical critique of modernity and capitalism, arguing that history is a continuous process of struggle and change driven by underlying societal contradictions. They view liberal democracy as a form of domination and advocate for a radical transformation of society. In contrast, Fukuyama's